2021
DOI: 10.2147/copd.s300693
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of COPD Phenotypes in Serbia

Abstract: Background Establishing a regional/national/international registry of patients suffering from chronic obstructive pulmonary disease (COPD) is essential for both research and healthcare, because it enables collection of comprehensive real-life data from a large number of individuals. Objective The aim of this study was to describe characteristics of COPD patients from the Serbian patient registry, and to investigate actual differences of those characteristics among the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…By contrast, 29.1% of patients with ACO were not receiving ICS, despite the benefits that ICS has demonstrated in this group of patients. Similarly, in other countries, it has been observed that treatment patterns differ among the phenotypes and ICS has not been used as widely as expected in the ACO phenotype [ 14 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 98%
“…By contrast, 29.1% of patients with ACO were not receiving ICS, despite the benefits that ICS has demonstrated in this group of patients. Similarly, in other countries, it has been observed that treatment patterns differ among the phenotypes and ICS has not been used as widely as expected in the ACO phenotype [ 14 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 98%
“…There have been many studies evaluating the prevalence of COPD phenotypes, most of these studies have a larger proportion of NON-AE phenotypes than the remaining phenotypes. Research by author Lazic in 2020 in Serbia [8] showed the proportion of ACO, NON-AE, AE-CB and AE-NON-CB phenotypes, respectively, 8.7%, 49.3%, 12.3%, and 29.7%. We found that patients with AE phenotypes accounted for a higher proportion than the remaining phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated sample size for the study was 124 based on the proportion of patients with the ACO phenotype of 8.8 % (ACO accounted for the lowest of the four phenotypes) in a 2016 study in Serbia by Zorica Lazic et al, with a class I error of 5% and an accuracy of 5% [8]. The attrition rate (dropout or loss to follow-up) was expected to be about 25%.…”
Section: -Sample Size Sampling Methodsmentioning
confidence: 99%
“…COPD adversely affects the quality of life of patients, decreasing the number of Disability Adjusted Life Years (DALY) one can get during lifetime [2]. A number of countries organized national registries of COPD patients, showing a relatively high prevalence of this disease, which ranges between 4 and 5% [3][4][5]. Numerous factors contribute to the development of COPD.…”
Section: Introductionmentioning
confidence: 99%